Penerapan Alat Peraga untuk Mengatasi Miskonsepsi Matematika pada Materi Bangun Ruang Siswa Kelas VII SMP Kristen Karuni - Damma, Stefanus Umbu; Making, Samuel Rex Mulyadi; Lubur, Dorothea Novia Ludo; Lede, Yulius Keremata (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The purpose of this study is to determine the extent of understanding students in the application of teaching aids to overcome mathematical misconceptions in material on the construction of grade VII students of Karuni Christian Middle School. The type of research used is classroom action research (CAR). The subjects in this research are the class VII and the object of this research is the application of teaching aids to overcome Mathematical misconceptions in the material on shapes of grade VII students of Karuni Christian Middle School. The data collection technique is using tests, in the form of (post-test and pre-test) observation sheet. Data analysis techniques are carried out at the learning completion stage individual and classical. The results of the study can be concluded from both cycles of learning outcomes in using teaching aids for each student in working on test questions have different understandings. This can be seen from the results of the first cycle test of participants students have not been able to solve the given mathematics problems and in the cycle II students can solve the problems they encounter and are able to overcome them misconception.